Natural Extracts from White Common Bean (Phaseolus vulgaris L.) Inhibit 3T3-L1 Adipocytes Differentiation - Zhenxing Shi; Xin Zhang; Yingying Zhu; Yang Yao; Guixing Ren (Applied Sciences, 2020)
Background: Recent studies have shown that the consumption of common bean (Phaseolus vulgaris L.) foods plays an essential role in the prevention and treatment of obesity. Methods: In this study, different natural extracts that include common bean polyphenol-rich extract (CBP), α-amylase inhibitor-rich extract (α-AIE), and non-starch polysaccharides-rich extract (NSP) were isolated. Their effects on 3T3-L1 adipocytes differentiation were evaluated, respectively. Results: The results showed that CPB reduced the lipid content in the mature adipocytes to 79.29% (150 μg/mL) and 35.13% (300 μg/mL), and α-AIE reduced it to 90.20% (2 mg/mL) and 68.28% (4 mg/mL), while NSP exhibited an auxo-action, suggesting that both CBP and a-AIE inhibited 3T3-L1 adipocytes differentiation. Additionally, CBP significantly suppressed (p < 0.05) the mRNA expression level and the protein expression level of peroxisome proliferator-activated receptor γ (PPARγ), CCAAT-enhancer-binding protein α (C/EBPα), sterol-regulatory element binding proteins 1 c (SREBP-1c), lipoprotein lipase (LPL), and fatty acid binding protein (ap2). Meanwhile, α-AIE only showed significant suppression effects on PPARγ, C/EBPα, and ap2 at the high dose of 4 mg/mL (p < 0.05). Conclusions: These findings indicate that CBP, from white common bean, might be the major component responsible for the inhibitory effects on adipocyte differentiation.